2014
DOI: 10.3379/msjmag.1403r001
|View full text |Cite
|
Sign up to set email alerts
|

CPP-GMR study of half-metallic full-Heusler compound Co2(Fe,Mn)Si

Abstract: Co2FexMn1-xSi (CFMS) is one of the most attractive highly spin-polarized materials since large tunnel magneto-resistance and giant magneto-resistance have been recenltly observed in the devices using CFMS electrodes. In this study, we investigated the dependence of CPP-GMR in CFMS/Ag/CFMS on Fe composition x and annealing temperature Tann for CFMS electrodes. The highest intrinsic MR ratio of 55% and ΔRA of 17.2 mΩ•µm 2 were achieved at x = 0.5 and Tann = 550°C. Finally, we compared the results on CPP-GMR with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Silver has one of the best energy level matches to magnetic Heusler alloys for optimised GMR performance [11,23]. Therefore to maximise any potential GMR the tungsten spacer layer has been replaced with one of silver, with thicknesses 3 nm and 5 nm.The samples were deposited at T S = 335 K in order to maximise the coercivity difference between the two layers.…”
Section: Resultsmentioning
confidence: 99%
“…Silver has one of the best energy level matches to magnetic Heusler alloys for optimised GMR performance [11,23]. Therefore to maximise any potential GMR the tungsten spacer layer has been replaced with one of silver, with thicknesses 3 nm and 5 nm.The samples were deposited at T S = 335 K in order to maximise the coercivity difference between the two layers.…”
Section: Resultsmentioning
confidence: 99%
“…The half-metallic band gap sensitively changes depending on the degree of chemical disorder [18]; hence, obtaining high degree of L2 1 order is essential to achieve the half-metallicity at room temperature. Although the half-metallic band gap in the L2 1 structure is theoretically predicted to be preserved in the B2 structure in some of Co 2 FeZ and Co 2 MnZ-types alloys, significant improvement of DRA with increasing the degree of L2 1 -order by post-annealing above 500°C was reported in the CFMS/Ag/CFMS [5] and CFGG/Ag/CFGG [7] tri-layer structures.…”
Section: Introductionmentioning
confidence: 94%
“…Heusler alloys [2] are the most promising material because of their high Curie temperatures well above room temperature (RT). High magnetoresistance (MR) ratios and large spin accumulation signals reflecting the half-metallicity of Co-based Heusler alloys have been clearly demonstrated in current perpendicular to plane giant magnetoresistance (CPP-GMR) [3][4][5][6][7][8][9], tunneling magnetoresistance (TMR) [10][11][12][13] and non-local spin-valve (NLSV) devices [14][15][16] using Co 2 MnSi (CMS), Co 2 Fe (Al 0.5 Si 0.5 ), Co 2 (Fe 0.4 Mn 0.6 )Si (CFMS), Co 2 Fe(Ga 0.5 Ge 0.5 ) (CFGG), and Co 2 FeSi as FM electrodes. Especially in the CPP-GMR devices using CFMS and CFGG, MR ratios over 50% at room temperature were reported, which are one order of magnitude higher than those using conventional FMs such as CoFe or NiFe.…”
Section: Introductionmentioning
confidence: 98%
“…15 Another critical subject to overcome is large temperature dependence of P . [5][6][7]12,[16][17][18][19] Experimental studies have reported that although an extremely high value of TMR ratio is demonstrated at low temperature in the MTJs consisting of the Heusler elec-trodes and MgO barrier, a significant reduction in TMR at room temperature is observed, for example, the TMR of 2010 % at 4.2 K, but it decreases to only 335 % at 290 K in Co 2 MnSi/MgO/Co 2 MnSi MTJ 7 and 2610 % at 4.2 K, but only 429 % at 290 K in Co 2 (Fe,Mn)Si/MgO/Co 2 (Fe,Mn)Si 20 . From the Jullièr model, the spin polarization P = 95 % (98 %) at low temperature decreases to P = 79 % (82 %) at room temperature for MTJs with Co 2 MnSi (Co 2 (Fe,Mn)Si) electrode.…”
Section: Introductionmentioning
confidence: 99%